PERTIWI DAN TIRTA MENGUKUHKAN KEMBALI NILAI TRI HITA KARANA DI BANJAR NEGARI DESA SINGAPADU TENGAH - Kadek Putri Oktaviana Melani; Pande Komang Lisa Tamara Sandi; I Putu Gede Putra Setiawan; I Gusti Lanang Raiditya Agung; Achmad Faisal Ramdani; I Made Mahardhika; Putu Agus Permanamiarta (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
Thematic Community Service Program (KKN) is a form of community service aimed at encouraging community empowerment through the application of knowledge and local wisdom. This activity was conducted in Banjar Negari, Singapadu Tengah Village, Sukawati District, Gianyar Regency, from February 18–March 12, 2026, by 14 students from the University of PGRI Mahadewa Indonesia (UPMI). The program, themed